Persepsi dan Faktor-Faktor Yang Mempengaruhi Wisatawan Mengunjungi Objek Wisata Tetempangan Hill Di Kab.Minahasa - DEISY CHRISTINA ANDIH (PolimdoSains, 2020)
Tetempangan Hill is one of the tourism objects in the land of Minahasa which becomes a favorite destination for both local, national and international tourists who want to enjoy the beauty of green hill view and the stretch of blue ocean. This research was conducted using Descriptive qualitative method and the data were collected using questionnaires distributed to respondents. The characteristics of tourists who visited Tatempangan Hill were dominated by male tourists with a percentage of 60 % and the remaining 40 % were female tourists and the tourist characteristics based on age were dominated by the tourists aged 15 to 29 years, followed by tourists aged 30 to 44 years. The tourists’ perceptions based on attraction (attractiveness), accessibility ( transportation), amenities ( facilities) were dominated by positive perceptions except the food and drink kiosks which were negative. The factors that motivated the tourists to visit Tatempangan Hill were ,firstly, to see the natural beauty and secondly , to accompany families and thirdly, to experience physical challenges , fourthly, to have relaxation /rest , fifthly , to enjoy something different and finally, to get closer to nature. It is suggested that the object operator add the menu sold at the food and drink kiosks considering that the tourists get problems with their food and drink needs since the kiosks only sell snacks and cup noodles.